Revision of the Agathidinae (Hymenoptera, Braconidae) of Vietnam, with the description of forty-two new species and three new genera - van Achterberg, Cornelis (Pensoft Publishers, 2010)
Abstract. The species of seventeen genera of Agathidinae (Braconidae) from Vietnam are revised: Agathis Latreille, 1804, Bassus Fabricius, 1804; Biroia Szépligeti, 1900; Braunsia Kriechbaumer, 1894; Camptothlipsis Enderlein, 1920; Coccygidium de Saussure, 1892; Coronagathis gen. n. (type species: Coronagathis cornifera sp. n.); Cremnops Foerster, 1862; Disophrys Foerster, 1862; Earinus Wesmael, 1837; Euagathis Szépligeti, 1900; Gyragathis gen. n. (type species: Gyragathis quyi sp. n.), Gyrochus Enderlein, 1920; Lytopylus Foerster, 1862; Therophilus Wesmael, 1837; Troticus Brullé, 1846, and Zelodia gen. n. (type species: Zelomorpha varipes van Achterberg & Maetô, 1990). Keys to the Vietnamese species are given. Sixty-five species are recognised, of which twelve species are newly recorded for Vietnam: Bassus albifasciatus (Watanabe, 1934), Coccygidium angostura (Bhat & Gupta, 1977), Cremnops atricornis (Smith, 1874), stat. n., Disophrys erythrocephala Cameron, 1900, Gyrochus yunnanensis Wang, 1984, Lytopylus romani (Shestakov, 1940), comb. n., Therophilus festivus (Muesebeck, 1953), comb. n., Therophilus javanus (Bhat & Gupta, 1977), comb. n., Therophilus lienhuachihensis (Chou & Sharkey, 1989), comb. n., Therophilus marshi (Bhat & Gupta, 1977), comb. n., Zelodia absoluta (Chen & Yang, 1998), comb. n. and Zelodia longidorsata (Bhat & Gupta, 1977), comb. n. Forty-two species are new to science: Agathis citrinisoma sp. n., Bassus albobasalis sp. n., Bassus albozonatus sp. n., Biroia soror sp. n., Braunsia bicolorata sp. n., Braunsia devriesi sp. n., Braunsia maculifera sp. n., Braunsia nigrapiculata sp. n., Braunsia pumatica sp. n., Camptothlipsis hanoiensis sp. n., Coronagathis cornifera sp. n., Earinus aurantius sp. n., Earinus brevistigmus sp. n., Euagathis flavosoma sp. n., Disophrys maculifera sp. n., Disophrys quymanhi sp. n., Disophrys rhinoides sp. n., Gyragathis quyi sp. n., Therophilus annuliferus sp. n., Therophilus cattienensis sp. n., Therophilus contrastus sp. n., Therophilus crenulisulcatus sp. n., Therophilus depressiferus sp. n., Therophilus elongator sp. n., Therophilus levisoma sp. n., Therophilus marucae sp. n., Therophilus mellisoma sp. n., Therophilus nigrolineatus sp. n., Therophilus nuichuaensis sp. n., Therophilus parasper sp. n., Therophilus planifrons sp. n., Therophilus punctiscutum sp. n., Therophilus robustus sp. n., Therophilus rugosiferus sp. n., Therophilus scutellatus sp. n., Troticus alloflavus sp. n., Troticus giganteus sp. n., Zelodia albobasalis sp. n., Zelodia anginota sp. n., Zelodia bicoloristigma sp. n., Zelodia brevifemoralis sp. n. and Zelodia flavistigma sp. n. The following new synonyms are proposed: Euagathis nigrithorax Bhat & Gupta, 1977, Euagathis variabilis Enderlein, 1920, Euagathis variabilis var. tibialis Enderlein, 1920, Euagathis variabilis var. melanopleura Enderlein, 1920 and Euagathis variabilis var. sucarandana Enderlein, 1920 with Euagathis abbotti (Ashmead, 1900); Euagathis jinshanensis Chen & Yang, 2006 and Euagathis sharkeyi Chen & Yang, 2006, with Euagathis forticarinata (Cameron, 1899). The genus Amputostypos Sharkey, 2009, is synonymised with Coccygidium de Saussure, 1892, syn. n. The following new combinations are given: Bassus subrasa (Enderlein, 1920), comb. n., Gyragathis angulosa (Bhat & Gupta, 1977), comb. n., Lytopylus romani (Shestakov, 1940), comb. n., Therophilus annulus (Chou & Sharkey, 1989), comb. n., Therophilus asper (Chou & Sharkey, 1989), comb. n., Therophilus cingulipes (Nees, 1812), comb. n., Therophilus daanyuanensis (Chen & Yang, 2006), comb. n., Therophilus fujianicus (Chen & Yang, 2006), comb. n., Therophilus javanus (Bhat & Gupta, 1977), comb. n., Therophilus lanyuensis (Chou & Sharkey, 1989), comb. n., Therophilus luzonicus (Bhat & Gupta, 1977), comb. n., Therophilus muesebecki (Bhat & Gupta, 1977), comb. n., Therophilus rudimentarius (Enderlein, 1920), comb. n., Therophilus similis (Bhat & Gupta, 1977), comb. n., Therophilus sungkangensis (Chou & Sharkey, 1989), comb. n., Therophilus tanycoleosus (Chen & Yang, 2006), comb. n., Therophilus tonghuaensis (Chen & Yang, 2006), comb. n., Therophilus tongmuensis (Chen & Yang, 2006), comb. n., Therophilus transcasperatus (Chen & Yang, 2006), comb. n., Troticus latiabdominalis (Bhat, 1978),comb. n., Zelodia absoluta (Chen & Yang, 1998), comb. n., Zelodia achterbergi (Chen & Yang, 2006), comb. n., Zelodia albopilosella (Cameron, 1908), comb. n., Zelodia chromoptera (Roman, 1913), comb. n., Zelodia nihonensis (Sharkey, 1996), comb. n., Zelodia cordata (Bhat & Gupta, 1977), comb. n., Zelodia diluta (Turner, 1918), comb. n., Zelodia dravida (Bhat & Gupta, 1977), comb. n., Zelodia exornata (Turner, 1918), comb. n., Zelodia longidorsata (Bhat & Gupta, 1977), comb. n., Zelodia longiptera (Yang & Chen, 2006), comb. n., Zelodia maculipes (Cameron, 1911), comb. n., Zelodia nigra (Bhat & Gupta, 1977), comb. n., Zelodia philippinensis (Bhat & Gupta, 1977), comb. n., Zelodia reticulosa (Yang & Chen, 2006), comb. n., Zelodia quadrifossulata (Enderlein, 1920), comb. n., Zelodia ruida (Sharkey, 1996), comb. n., Zelodia similis (Bhat & Gupta, 1977), comb. n., Zelodia penetrans (Smith, 1860), comb. n. and Zelodia varipes (van Achterberg & Maetô, 1990), comb. n.